Public Service Domain: Exploration Study on The Role of Public Relations in Indonesia - Sugeng Suharto; Prasetyono Hendriarto; Firdaus Yuni Dharta; Marulam MT Simarmata; Mateo Jose A. Vidal (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
Public relations (PR) professionals used to rely mainly on newspapers, radio, and television for their campaigns before digitization. However, since the invention of the internet, public relations has been converted into digital PR. In this circumstance, public relations must adapt and migrate from traditional to digital media. This exploratory study examines public relations in Indonesia by conducting a survey and understanding the role of public relations that Indonesian public relations practitioners usually practice. Through the lens of systems theory, this study aims to investigate how 1) Public Relations is organized by Indonesian professionals, 2) The role of Public Relations in Indonesia, 3) Understanding and Professional Public Relations in Indonesia. This study uses a quantitative approach with survey methods related to Indonesian public relations practitioners. The data for this study were obtained using Qualtrics. According to the findings, Indonesian professionals who organize public relations participate in public relations activities with input, throughput, and output methods. In Indonesia, the job of public relations is linked to digital clippings that are crucial for an institution or institution and hosting corporate events as a tactic to improve the image. Meanwhile, in Indonesia, the definition and profession of public relations can impact how the job is conducted, and the country currently lacks a comprehensive public relations education program.Keywords: Public service domain, role of public relations, Indonesia ABSTRAKPara profesional hubungan masyarakat (PR) biasanya mengandalkan surat kabar, radio, dan televisi untuk kampanye mereka sebelum digitalisasi. Namun, sejak penemuan internet, PR telah diubah menjadi PR digital. Dalam keadaan ini, humas harus beradaptasi dan bermigrasi dari media tradisional ke media digital. Studi eksploratif ini mengkaji humas di Indonesia dengan melakukan survei dan memahami peran humas yang biasa dipraktikkan oleh praktisi humas Indonesia. Melalui lensa teori sistem, penelitian ini bertujuan untuk mengetahui bagaimana 1) Humas diselenggarakan oleh profesional Indonesia, 2) Peran Humas di Indonesia, 3) Pengertian dan Profesional Humas di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terkait dengan praktisi humas Indonesia. Data untuk penelitian ini diperoleh dengan menggunakan Qualtrics. Berdasarkan temuan, profesional Indonesia yang menyelenggarakan humas berpartisipasi dalam kegiatan humas dengan metode input, throughput, dan output. Di Indonesia, pekerjaan humas terkait dengan kliping digital yang sangat penting bagi sebuah institusi atau institusi dan menyelenggarakan acara perusahaan sebagai taktik untuk meningkatkan citra. Sementara itu, di Indonesia, definisi dan profesi humas dapat berdampak pada bagaimana pekerjaan itu dilakukan, dan negara saat ini masih kekurangan program pendidikan humas yang komprehensif.Kata Kunci: Domain layanan public, peran humas, Indonesia